Push-mode printhead using magnetic linear actuator - Mana Saedan (2018)
A magnetic linear actuator drop-on-demand printhead with interchangeable components is designed and fabricated. The manufacturing processes of all parts are carried out with simple techniques. A droplet generation relies on a linear motion from a piston inside a printhead chamber that causes a pressure wave to push an ink out from a nozzle-aperture. The motion is actuated by a voice coil liked actuator. The voltage applied across the actuator is significantly lower than the piezo actuator. The interchangeable components enable rapid configuration of a printhead to suit wide range of ink-materials. The prototype of our printhead was tested with inks prepared from glycerin-water solutions. The operability of the printhead was evaluated at actuated time ranging from 2-100 milliseconds. Our printhead was able to jet a single droplet of ink with viscosity up to 35 mPa.s. The drop size is comparable to other types of printheads. © (2014) Trans Tech Publications, Switzerland.